Two new Pogonocherus species (Coleoptera: Cerambycidae) from Baltic amber - Vitali, Francesco (Baltic Journal of Coleopterology, 2022)
Two new fossil cerambycids, Pogonocherus simplex sp. n. and Pogonocherus scutellaris sp. n. (Lamiinae: Pogonocherini) are described based on specimens preserved in Baltic amber. Morphological comparison is made with the extant congeners. Phylogenetic and palaeobiological remarks on the genus Pogonocherus Dejean, 1821 are added.